The Role of Global Ambassador and Brand Ambassador for Indonesian and Malaysian Youth - Farida Nurfalah; M. Nuruzzaman; Siti Khumayah; Rhevallino Daneztha Sulintang; Mohd Naufal Bin Yunos (PT Publikasiku Academic Solution, 2024)
The growing digital era, the role of influencer marketing has become one of the most effective marketing strategies and one of the important aspects in influencer marketing is the involvement of Global Ambassadors and Brand Ambassadors. This study aims to explore the implementation of the role of Global Ambassadors and Brand Ambassadors for Young People in Indonesia and Malaysia. The research methodology was carried out through the first stage, namely observation, development and use of the theory of global ambassadors and brand ambassadors ranging from providing testimonials, providing encouragement and reinforcement (Endorsement), acting as actors in the advertising topics they represent. The second stage is to test the theory through interviews to get feedback, visual representations, and problem-solving creativity that can identify opportunities that exist and be applied in business. The results of this study show that Global ambassadors play a major role for Indonesian and Malaysian youth, especially in shaping their lifestyle image and identity, encouraging consumption of international products, and shaping global trends. However, young people retain local cultural values that influence their perception of products and brands.